Optical microsphere resonators and laser frequency stabilization - Ilchenko, V.S. (Conference Proceedings. LEOS '97. 10th Annual Meeting IEEE Lasers and Electro-Optics Society 1997 Annual Meeting, 1997)
Following the extensive study of the physics of Mie resonances in microdroplets, high-Q whispering-gallery (WG) modes in solid-state microspheres since first demonstrations in the eighties have become a hot subject of research stimulated by the interest of quantum optics, cavity QED and photonics. This report focuses on the properties of microspheres relevant to their possible application for laser frequency stabilization; presented are preliminary experimental results on using optical feedback from high-Q microspheres for frequency locking in semiconductor lasers.